An Infrared and Raman Spectroscopic Investigation of Copper II Tetracyanonickelate Complexes ofalpha beta and gamma picoline - AKYÜZ, SEVİM (Kluwer Academic Publishers, 1986)
Copper(II) dipicoline tetracyanonickelate complexes, CuL2Ni(CN)4 (L=α,β- orγ-picoline), have been prepared for the first time and their infrared and Raman spectra are reported. Their structure consists of polymeric layers of {Cu-Ni(CN)4}∞ with picoline molecules bound directly to the copper. It is proposed that the Cu-NC bonds are in two nonequivalent pairs in trans positions. Low temperature (83K) IR spectra have also been recorded and it is noted that the Ni(CN)4 group frequencies increase with decreasing temperature while the picoline frequencies are insensitive to temperature.
Keywords: IR and Raman spectra; tetracyanonickelate complex; α-,β- andγ-picoline complexes